Dataset: Unveiling the Landscape of Online Business and CSR Strategy Research: A Comprehensive Analysis - Aulia Sarah Azizah; Mochammad Tanzil Multazam (Proceedings of The ICECRS, 2022)
This data article investigates the prevalence of journal articles related to online business and CSR strategy. Using lens.org, a total of 4,929 documents were initially identified, which were further refined to 203 documents related to the law subject. The analysis reveals the most active institutions, authors, countries, and publishers in the field. The findings underscore the importance of business ethics and corporate social responsibility in the context of online businesses, providing valuable insights for researchers, policymakers, and educators.Highlights: The study identified 203 law-related journal articles focused on online business and CSR strategy. The University of Nottingham emerged as the top institution in the field, contributing significantly to business ethics and corporate social responsibility research. The analysis highlights the growing importance of business ethics and corporate social responsibility in the context of online businesses.